2017
DOI: 10.1186/s12938-017-0331-1
|View full text |Cite
|
Sign up to set email alerts
|

Signal-to-noise ratio evaluation of magnetic resonance images in the presence of an ultrasonic motor

Abstract: BackgroundSafe robot-assisted intervention using magnetic resonance imaging (MRI) guidance requires the precise control of assistive devices, and most currently available tools are rarely MRI-compatible. To obtain high precision, it is necessary to characterize and develop existing MRI-safe actuators for use in a high magnetic field (≥3 T). Although an ultrasonic motor (USM) is considered to be an MRI-safe actuator, and can be used in the vicinity of a high field scanner, its presence interferes with MR images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…To deal with the MRI compatibility, in addition to hydraulic 56,57 or pneumatic 27,5860 actuators, other types such as ultrasonic or piezoelectric motors, which have been the favorite so far due to their non-magnetic core, short response time and small size 61,62 , could have been utilized. However, no commercially available piezo motors are available for the 14.1 T MRI scanner and it has been recently shown that piezo motors could induce geometric distortions in MR images even at a lower magnetic field strength 63,64 . Also, different MRI sequences could have effects on the behavior of ultrasonic motors 65 .…”
Section: Discussionmentioning
confidence: 99%
“…To deal with the MRI compatibility, in addition to hydraulic 56,57 or pneumatic 27,5860 actuators, other types such as ultrasonic or piezoelectric motors, which have been the favorite so far due to their non-magnetic core, short response time and small size 61,62 , could have been utilized. However, no commercially available piezo motors are available for the 14.1 T MRI scanner and it has been recently shown that piezo motors could induce geometric distortions in MR images even at a lower magnetic field strength 63,64 . Also, different MRI sequences could have effects on the behavior of ultrasonic motors 65 .…”
Section: Discussionmentioning
confidence: 99%
“…We further analyzed the effects of motor orientations in Refs. [18], [19].
Fig. 3Eight consecutive slices of the phantom in the presence of the motor scanned with a T2W sequence to indicate the types of generated image artifacts.
…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative analyses of temperature change, geometric distortions of MR images, and signal-noise-ratio of USM have been reported in [28][29][30].…”
Section: Discussionmentioning
confidence: 99%